The Effect Of KAP Model On The Occurrence Of Tuberculosis In The Working Area Of Padang Serai Health Center In Bnegkulu City In 2025 - Meta Rarosa; Jipri Suyanto; Fery Surahman (Journal of International Public Health, 2026)
Intoduction: Tuberculosis (TB) is one of the leading causes of death from infectious diseases worldwide. According to data from the Ministry of Health of the Republic of Indonesia (2023), the national prevalence of pulmonary TB is recorded at 0.30%, with Central Papua having the highest prevalence at 1.15% and Bali the lowest at 0.09%. According to WHO data (2024), Southeast Asia accounts for 46% of the total global TB cases. This situation indicates that TB control remains a top priority, especially in developing countries like Indonesia. This study aims to determine the effect of the KAP model on tuberculosis occurrence in the Working Area of Padang Serai Health Center of ​​Bengkulu City in 2025. Method: The method used in this study was a quantitative analytical study with a cross-sectional approach, with a sample of 91 people using total random sampling. Data analysis used Chi-square and logistic regression. Result and Discussion: Univariate analysis results showed that respondents had good knowledge (58.2%), favorable attitudes (59.3%), and good behavior (65.9%). Bivariate analysis results showed a significant correlation between knowledge (p=0.000), attitude (p=0.000), and behavior (p=0.001) and the occurrence of pulmonary TB. Multivariate analysis results showed that only attitude had a statistically significant effect on the incidence of pulmonary TB (p=0.013; OR=7.978; 95% CI: 1.537–41.428). Conclusion: It is expected that community health centers can coordinate with health workers to provide health education regarding the causes of tuberculosis and tuberculosis prevention, as well as encourage the community to actively participate in tuberculosis prevention activities at the health center.